Dissemination Strategy for Three Spotted Tilapia in Zambia - Komugisha, Basiita Rose; Benzie, John; Harburg, Sam Haburg; Chungu, Patience; Malambo, Tom (WorldFish, 2022)
Background & Report Objectives The Zambia Aquaculture Enterprise Development Project (ZAEDP) was launched by the Government of Zambia in 2017 with funding from the African Development Bank. As part of ZAEDP, The Zambian government, with support from WorldFish as technical advisors have established a genetic improvement program for Three Spotted Tilapia, a key indigenous Tilapia species perceived to possess good potential for aquaculture production within Zambian production systems. The genetic improvement program seeks to establish the foundation for future supply of genetically improved Three Spotted Tilapia fingerlings (seed) to the Zambian aquaculture industry.This report comprises the two primary areas of scope described below. 1. Assess the status and potential of the Zambian aquaculture industry, identifying the market opportunity for genetically improved Three Spotted Tilapia seed and subsequent requirements for development of a commercially sustainable breeding program. 2. Identify appropriate industry monitoring systems, data requirements and applicable standards/protocols to support the operations and management of the hatchery sector, particularly the genetic improvement nucleus.